Short communicationAcute ST-segment elevation myocardial infarction treated with delayed angioplasty in a patient with anomalous origin of the right coronary artery in the early phase after kidney transplantation - Roik, Marek; Wretowski, Dominik; Łabyk, Andrzej; Kostrubiec, Maciej; Pływaczewska, Magdalena; Sawicki, Rafał; Jankowski, Krzysztof; Pruszczyk, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
This case demonstrates a rare anomalous of origin of right coronary artery from the left sinus of Valsalva in patients who underwent kidney transplantation complicated by an acute ST elevation myocardial infarction treated with delay angioplasty.